Предмет: Алгебра,
автор: RVNG
Упростите выражение ( 1/a-6 - 1/a+6 ) : 2/a+6
Ответы
Автор ответа:
0
1)приводим к общему знаменателю в скобках:
(a+6)-(a-6) (a^2-36) = a+6-a+6 (a^2-36) =12 (a^2-36)
2) 12(a-6)*(a+6) : 2/a+6= 12(a-6)*(a+6) *a+62/
сокращаем на a+6 и на 2, получаем:6(a-6)
(a+6)-(a-6) (a^2-36) = a+6-a+6 (a^2-36) =12 (a^2-36)
2) 12(a-6)*(a+6) : 2/a+6= 12(a-6)*(a+6) *a+62/
сокращаем на a+6 и на 2, получаем:6(a-6)
Похожие вопросы
Предмет: Английский язык,
автор: marianne15
Предмет: История,
автор: lydmyla2008
Предмет: Математика,
автор: angelinagrishaeva
Предмет: Математика,
автор: Alesyavk
Предмет: География,
автор: skro